(3GdSLd GdhGQO Edi fUQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUd cJGH SjOi GdTjN GdaGVd CWGd Gddg HbGg hCOGe JCjjOg hfYeGg hhbaJ Ydi LejYg hMeOJ Gddg Ydi ceGd SdGeJg s
(3BNQgG (B:s
(3adG JLYd Ydi bdHc KbdkG ef CeQ GHf eYdG adGHO jHdZc eG jMd Hg hGdMeO ddg hMOg hUdhGJg Ydi QShdg hBdg GdWGgQjf hgh MSHfG hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B93s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis